Treasures from the Oxus the art and civilization of Central Asia - Vidale, Massimo 1956- (I.B. Tauris, 2017)
In history, this grand arterial 1500-mile waterway was always seen as the natural frontier between the northern provinces of the Iranian empires and the outer Turanian lands. It was for centuries central to Achaemenid and later Persian power. But, as the author shows, it has a prehistory which goes very much further back: and a succession of skilled yet still elusive Bronze Age cultures flourished here well before the rise of Cyrus the Great in the 6th century BCE. This richly illustrated book explores the fascinating history, art and archaeology of the region, including its primal trade in silk and foodstuffs; the mineral wealth of the Oxus basin; its exotic myths and beliefs; and the converging tribes and peoples which led to a new stability, economic growth and urbanism. The volume contains 150 full-colour photographs of notable artefacts, including silver decorated vessels, inlaid stone pots, agate beads and 25 'Bactrian Princesses': remarkable statuettes made in chlorite and limestone. Most of these rare objects have never been seen, let alone published, before
Keywords: Funde; Bronzezeit; Archäologie; Zentralasien; Amu-Darja-Gebiet; Baktrien; Margiana; Asia, Central / Antiquities; Amu Darya / Antiquities